Ngô Tất Tố toàn tập T.4. (Hà Nội : Văn học, 1996)
Tiểu thuyết: Trong rừng nho. Tắt đèn. Lều chõng.
Keywords: Ngô Tất Tố, -- 1894-1954.; Ngô Tất Tố; Văn học Việt; Ngô Tất Tố, -- 1894-1954 -- Toàn tập; Văn học Việt